AN ATTEMPT TO UNDERSTAND THE CAUSES OF EFL STUDENTS’ WRITING MISTAKES - Kaddeche- Benzoukh Assia, HALIMA (University of El-oued, 2016)
Abstract Teachers and students admit that in any EFL classroom there might be some of the students’ writing mistakes. The present paper comes to shed light on the main causes or that lead EFL learners to commit the same writing mistakes. What is more is that the students' mistakes are sometimes the same previously corrected by their teachers. Hence, this study aims at detecting whether the teacher’s method is the main reason behind these mistakes. Moreover, this study tries to suggest a more effective strategy to deal with them. The study is carried out with first-year students of English at Kasdi Merbah University of Ouargla. To figure out the main causes behind committing of these mistakes, the selected sample is interviewed for fortyfive minutes. The interview’s findings reveal that first-year students of English keep committing the same writing mistakes because of anxiety, language complexity, L1 interference and the teacher’s feedback practices المعلمون والطالب يعترفون بأن في الفصول الدراسية للغة اإلنجليزية كلغة أجنبية قد تكون هناك بعض أخطاء الكتابة لدى الطالب. وتأتي هذه الورقة لتسليط الضوء على األسباب الرئيسية التيتؤدي إلى ارتكاب نفس أخطاء الكتابة. ما هو أكثر من ذلك هو أن أخطاء الطالب في بعض األحيان نفسها المصححة من قبل معلميهم. وتهدف هذه الدراسة إلى الكشف عن ما إذا كانت طريقة المعلم هي السبب الرئيسي وراء هذه األخطاء. وعالوة على ذلك، تحاول هذه الدراسة إيجاد إستراتيجية أكثر فعالية للتعامل مع أخطاء الكتابة. وأجريت الدراسة مع طالب السنة األولى قسم اللغة اإلنجليزية في جامعة قاصدي مرباح ورقلة.
THE CASE OF FIRST YEAR STUDENTS OF ENGLISH AT KASDI MERBAH UNIVERSITY- OUARGLA
Keywords: writing mistakes, EFL classroom students, teaching, anxiety, L1 interference.: أخطاء الكتابة، وطالب اللغة اإلنجليزية كلغة أجنبية، الفصول الدراسية والتدريس، القلق، وتدخل اللغة األم.